Split‐calvarial osteopericranial flap for reconstruction following endoscopic anterior resection of cranial base. (28th October 2014) - Engle, Robert D.; Butrymowicz, Anna; Peris‐Celda, Maria; Kenning, Tyler J.; Pinheiro‐Neto, Carlos D.
Abstract : Objectives/Hypothesis: To conceive and critically evaluate an adaptation of the split calvarial osteopericranial flap for reconstruction following endoscopic endonasal resection of the anterior skull base. Study Design: Cadaveric anatomic study. Methods: Five cadavers were embalmed with methanol, and vasculature was injected with latex. Endoscopic endonasal resection of the anterior skull base was performed, followed by reconstruction with a unilateral osteopericranial flap and a contralateral conventional pericranial flap. Results: Rigid reconstruction was achieved in all specimens. Osteoplastic flap harvest was made more reliable by drilling the diploe below the graft with a curved bur. Dimensions of the bony flap were ideally shorter and wider than the defect, allowing for flap inset and rigid support by the orbits without compromise of the flap vascular supply. Endoscopic inset of the flap is feasible via nasion‐frontal osteotomy and inlay technique. Conclusion: Rigid anterior skull base reconstruction via split calvarial osteopericranial flap is adaptable to current endoscopic techniques. This provides more anatomic reconstruction than current methods and may lead to decreased complication rates following anterior skull base resection. Level of Evidence: N/A. Laryngoscope, 125:826–830, 2015